2017
DOI: 10.1007/s11145-017-9811-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the relationship of L1 learners’ performance in integrated writing with both independent listening and independent reading cognitive skills

Abstract: In recent decades, integrated language competence has been highlighted in the language curricula taught in schools and institutions, and the relationship between test-takers' performance on integrated tasks and comprehension sources has been much studied. The current study employed the frameworks of reading and listening comprehension processes to examine the difference between the effects of reading competence and listening competence on integrated writing performance. A total of 152 Secondary 5 students from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
3
22
0
1
Order By: Relevance
“…Similarly, successful writers can use dictionaries and thesauruses, they enjoy writing, and they find it convenient to describe what they say. Past literature, for example, indicated that cognitive reading skills have much effect on the performance of the student and are essential in performing the combined writing assignment than cognitive listening skills (Cheong et al, 2018). The advanced error factor seems more responsible than the essential error factor for reading, writing, and oral language skills (Choi et al, 2017).…”
Section: Reading and Writing Skillsmentioning
confidence: 99%
“…Similarly, successful writers can use dictionaries and thesauruses, they enjoy writing, and they find it convenient to describe what they say. Past literature, for example, indicated that cognitive reading skills have much effect on the performance of the student and are essential in performing the combined writing assignment than cognitive listening skills (Cheong et al, 2018). The advanced error factor seems more responsible than the essential error factor for reading, writing, and oral language skills (Choi et al, 2017).…”
Section: Reading and Writing Skillsmentioning
confidence: 99%
“…listening and reading as the receptive skills and Speaking and Writing as the productive skills are correlated. There has been a substantial amount of work that scrutinizes the connection between receptive and expressive language skills (Cheong, Zhu, & Liao, 2018;Pignot-Shahov, 2012;Anderson & Briggs, 2011;Tavares, 1990;Davies 1976). They all agreed that even though distinctions are made among language skills, for example, processing language input versus producing language output, yet the language construct is not separated.…”
Section: Introductionmentioning
confidence: 99%
“…The decision about choosing a secondary school can be influenced by a number of socio-demographic factors, such as gender, family background, family wealth, future expectations about education, labour market expectations and individuals’ characteristics. In the first stage, the agent decided their educational path as driven by their socio-demographic background (Cunha et al 2006 ; Ripamonti and Barberis 2018 ; Vittadini et al 2021 ), economic motivation (Van Uden et al 2014 ; Kearney and Levine 2014 ), as well as their perceived cognitive skills (Retelsdor et al 2011 ; Cheong et al 2018 ; Sawaki et al 2013 ). Several studies have found that non-cognitive skills, perceived cognitive skills, personal commitment and student engagement are precursors of learning, and they significantly impact students’ school performance (Denham et al 2012 ; Van Uden et al 2014 ; Wurdinger and Quereschi 2015 ).…”
Section: Aims and Methodsmentioning
confidence: 99%
“…Several studies assessed the impact of cognitive skills such as reading performance (Retelsdor et al 2011 ) and listening and writing (Cheong et al 2018 ; Sawaki et al 2013 ) on student motivation. Cheong et al ( 2018 ) found that cognitive reading skills contribute to performance more than cognitive listening . The study showed that three cognitive skills, elaborating , evaluating and creating , significantly correlated with integrated writing.…”
Section: Literature Reviewmentioning
confidence: 99%